The effectiveness of road calming devices in reducing vehicle speed - Nik Siti Aishah, Nik Li (2013)
This paper presents the assessment of effectiveness of traffic calming devices in reducing vehicle speed and in the same time to know the delay time when vehicle passing the traffic calming devices. Road accidents pose as a major health and social problem in this country and factors leads to accidents such as excessive speeding among the drivers. Therefore, the implementation of the traffic calming is widely used in improve road safety and to avoid negative effect. The site were chosen for each type of traffic calming devices implementation is speed hump at Jalan Perkampungan Permatang Badak and speed hump combination at Jalan Perkampungan Sungai Isap. Speeds and delay time of vehicle were collected at the selected sites to obtain the required data. Then, the data will be presented in the graph form with using Microsoft Excel 2010 and for statistical analysis to support the result using the same software. From the studies, it has found that the percentage reduction in the speed for the combination of speed hump is 55.8% and for speed hump was reduced to 49.6%. Delay time for speed hump is 5.84 seconds then followed by combination of speed hump is 6.49 seconds. This result is also proved by statistical test that shows the mean of speed reduction and delay for those two traffic calming devices are different from each other.